2013
DOI: 10.1177/1757975913483339
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of brief interventions on alcohol-related risks in occupational medicine

Abstract: Aim. To evaluate the effectiveness of brief interventions (BIs) in reducing alcohol use among hazardous drinkers consulting their occupational doctors. Materials and methods. Design: Randomized controlled trial with 12-month follow-up, conducted between November 2004 and September 2006. Setting: Fifteen French regional occupational medicine centers with 147 doctors and 157 assistants who were trained in BI and screening with the AUDIT questionnaire. Participants: We invited 33,488 individuals to fill out AUDIT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Anderson et al ( 37 ) found a reduction of drinking days per week (from 2.39 to 1.95), and Osilla et al ( 41 ) reported a significant reduction of peak drinks per occasion from 7.56 to 4.78 in the intervention group that received ASBI within an employee assistance program (EAP). Significant reduction in the AUDIT score after 12 months (6.59 vs. 7.55; p = 0.01) were found by Michaud et al ( 36 ), but without showing significant effects in reducing hazardous drinking. The face-to-face plus website intervention of Doumas and Hannah ( 24 ) reduced the number of drinks per weekend from 2.42 to 1.87.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Anderson et al ( 37 ) found a reduction of drinking days per week (from 2.39 to 1.95), and Osilla et al ( 41 ) reported a significant reduction of peak drinks per occasion from 7.56 to 4.78 in the intervention group that received ASBI within an employee assistance program (EAP). Significant reduction in the AUDIT score after 12 months (6.59 vs. 7.55; p = 0.01) were found by Michaud et al ( 36 ), but without showing significant effects in reducing hazardous drinking. The face-to-face plus website intervention of Doumas and Hannah ( 24 ) reduced the number of drinks per weekend from 2.42 to 1.87.…”
Section: Resultsmentioning
confidence: 74%
“…In this section, we provide an update of the results of our systematic review conducted in the framework for the EU project BISTAIRS 2 . Compared to the report published in 2012, the present study retrieved one additional article ( 36 ) in the workplace setting, resulting in 9 out of 3037 studies meeting our inclusion criteria (see Table 1 ). Key reasons for exclusion concerned, e.g., intervention characteristics (too long duration or general prevention), lack of effectiveness analyses, or inappropriate setting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Michaud (14) evaluó la eficiencia de las intervenciones breves en la reducción del consumo de alcohol en bebedores de riesgo que consultan a sus médicos de empresa. De 33.488 personas a las que se solicitó que contestaran al cuestionario AUDIT, los sujetos seleccionados fueron asignados aleatoriamente al grupo de intervención breve (IB) o al grupo de control.…”
Section: Iuhpe -Global Health Promotion Vol 20 Supp 2 2013unclassified